Caries Risk Assessment Item Importance: Risk Designation and Caries Status in Children under Age 6. (July 2016) - Chaffee, B.W.; Featherstone, J.D.B.; Gansky, S.A.; Cheng, J.; Zhan, L.
Caries risk assessment (CRA) is widely recommended for dental caries management. Little is known regarding how practitioners use individual CRA items to determine risk and which individual items independently predict clinical outcomes in children younger than 6 y. The objective of this study was to assess the relative importance of pediatric CRA items in dental providers' decision making regarding patient risk and in association with clinically evident caries, cross-sectionally and longitudinally. CRA information was abstracted retrospectively from electronic patient records of children initially aged 6 to 72 mo at a university pediatric dentistry clinic ( n = 3, 810 baseline; n = 1, 315 with follow-up). The 17-item CRA form included caries risk indicators, caries protective items, and clinical indicators. Conditional random forests classification trees were implemented to identify and assign variable importance to CRA items independently associated with baseline high-risk designation, baseline evident tooth decay, and follow-up evident decay. Thirteen individual CRA items, including all clinical indicators and all but 1 risk indicator, were independently and statistically significantly associated with student/resident providers' caries risk designation. Provider-assigned baseline risk category was strongly associated with follow-up decay, which increased from low (20.4%) to moderate (30.6%) to high/extreme risk patients (68.7%). Of baseline CRA items, before adjustment, 12 were associated with baseline decay and 7 with decay at follow-up; however, in the conditional random forests models, only the clinical indicators (evident decay, dental plaque, and recent restoration placement) and 1 risk indicator (frequent snacking) were independently and statistically significantly associated with future disease, for which baseline evident decay was the strongest predictor. In this predominantly high-risk population under caries-preventive care, more individual CRA items were independently associated with providers' risk determination than with future caries status. These university dental providers considered many items in decision making regarding patient risk, suggesting that, in turn, these comprehensive CRA forms could also aid individualized care, linking risk assessment to disease management. Knowledge Transfer Statement: Caries risk assessment (CRA) is widely recommended for patient-tailored, prevention-focused caries management. Studies show mixed predictive performance of pediatric CRA instruments, but little is known regarding how information captured in CRA forms guides clinical decision making. This study, in high-caries prevalence 6- to 72-mo-olds, demonstrates the following: 1) most items in a CRA instrument were independently associated with practitioners' risk designations, 2) practitioners' risk designations were significantly associated with future disease, and 3) of baseline measures associated with future caries, evident decay was the strongest independent indicator of future caries status. Although current disease (resulting from existing pathological and protective factor imbalance) may sufficiently predict future caries status in populations, other CRA items incorporated during risk categorization could aid practitioners to develop individualized intervention strategies against identified risk factors.